THE IMPORTANCE OF RAW MATERIALS INVENTORY SUPERVISION FOR PRODUCTION PROCESS - Bina Andari (Universitas Islam Balitar, 2016)
This paper describes the importance of the raw materials Inventory supervision for production process. The concepts described in this paper was studied using the descriptive theoretical analysis. It is concluded that (1) Raw Materials Inventory control is highly needed by both small and big companies to take care of the production process stabilization; (2) The production process will find problems when there is no good control of the Inventory. This causes anstable production process effecting finnace of the companies. The long period of materials inventory causes campany loss. On the other hand, small amount of inventory will also cause the production processes stop. Such situation will also influence marketting and the supply to the consumers; (3) Unstable producation process will cause unstable product supply in the market, and (4) To ensure that the consumers ’ needs are continuously completed, control of the raw materials inventory needs to be done and maintained.